Frequency, demographics, diagnoses and consultation patterns associated with low-acuity attendances in German emergency departments: a retrospective routine healthcare data analysis from the INDEED project - Patrik Dröge; Anna Slagman; Felix Greiner; Martin Möckel; Liane Schenk; Anna Schneider; Thomas Keil; Stephanie Roll; Rainer Röhrig; Felix Walcher; Reinhard Busse; Johannes Drepper; et al. (BMJ Open, 2024)
Objective Evidence suggests interventions targeting low-acuity attendances have been hampered by insufficient characterisation of potential target groups. This study aimed to estimate the frequency of low-acuity emergency department (ED) attendances and to provide an overview of their demographic, diagnosis and consultation patterns.Design Observational analyses of routine healthcare data.Setting German EDs.Participants Adult patients with statutory health insurance who visited the ED of 16 participating hospitals in 2016.Main outcome measures Frequency, demographics, diagnoses and consultation patterns of low-acuity and high-acuity attendees.Main results Of the 454 747 ED visits, 370 756 visits (50.1% female) were included for analysis. Four participating hospitals had to be excluded due to the lack of data that were necessary for the stepwise approach to define low and high acuity. We identified 101 337 visits as low acuity (27.3%) and 256 876 as high acuity (69.3%), whereas 12 543 (3.4%) could not be classified. The proportion of attendees classified as low acuity decreased with age (highest at 40.6% in the age group <35 years). The proportion of women and men was 50% in both acuity categories, respectively (50 654 of all low-acuity and 128 427 of all high-acuity contacts). The highest proportion of low-acuity presentations was observed during the weekend (average of 18.6% per day), compared with an average of 12.5% on weekdays. The most common diagnoses (back pain, abdominal and pelvic pain) were similar in both low-acuity and high-acuity groups.Conclusion Our study provides further evidence that younger age is associated with low-acuity presentation in German EDs. Age-specific intervention strategies are needed to ease the burden on urgent care facilities. The similar spectrum of diagnoses between low-acuity and high-acuity patients suggests a so far under-recognised higher importance of severity.Trial registration number DRKS00022969.